2011
DOI: 10.1021/ja2039562
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Ti0.7Mo0.3O2 Support Enhances Electron Transfer to Pt: High-Performance Catalyst for Oxygen Reduction Reaction

Abstract: The slow rate of the oxygen reduction reaction (ORR) and the instability of Pt-based catalysts are two of the most important issues that must be solved in order to make proton exchange membrane fuel cells (PEMFCs) a reality. Additionally, the serious carbon corrosion on the cathode side is a critical problem with respect to the durability of catalyst that limits its wide application. Here, we present a new approach by exploring robust noncarbon Ti(0.7)Mo(0.3)O(2) used as a novel functionalized cocatalytic supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
263
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 391 publications
(277 citation statements)
references
References 57 publications
14
263
0
Order By: Relevance
“…% H 2 /He environment (flow rate of 40 mL.min -1 ). Pt L III -edge measurements data collection modes, and calculation of errors were all done as per the guidelines set by the International XAFS Society Standards and Criteria Committee [8,10,11,12].…”
Section: X-ray Absorption Spectroscopy (Xas) Measurementsmentioning
confidence: 99%
“…% H 2 /He environment (flow rate of 40 mL.min -1 ). Pt L III -edge measurements data collection modes, and calculation of errors were all done as per the guidelines set by the International XAFS Society Standards and Criteria Committee [8,10,11,12].…”
Section: X-ray Absorption Spectroscopy (Xas) Measurementsmentioning
confidence: 99%
“…Low and high graphitic carbon are, e.g., carbon black (CB), single-walled or multi-walled carbon nanotube (CNT), graphene oxide (GO) [55,[163][164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179][180][181][182] and carbon nitride (CN) [183][184][185][186] among others. The semi-conducting oxides, such as TiO 2 , doped-TiO 2 and doped-SnO 2 , have been reported as support for catalytic centers [187][188][189][190][191][192][193]. The conductivity of oxides can be improved by synthesizing oxide/carbon composites [194].…”
Section: Oxygen Reduction Reaction-orr and Carbon Supportsmentioning
confidence: 99%
“…Hwang et al 79 have synthesized Pt-Ti 0.7 Mo 0.3 O 2 NHSs through a sol-gel protocol and utilized them in the electro-catalysis of oxygen reduction reactions. They found that their NHSs performed much better than the conventional Pt/C catalyst.…”
Section: Catalytic Propertiesmentioning
confidence: 99%